2000
DOI: 10.3171/jns.2000.93.4.0711
|View full text |Cite
|
Sign up to set email alerts
|

Use of titanium mesh for reconstruction of large anterior cranial base defects

Abstract: The authors evaluated the role of titanium mesh used in combination with vascularized pericranium to provide rigid support during reconstruction of anterior skull base defects. Thirteen patients with large anterior skull base defects caused by tumor invasion or traumatic injury involving the cribriform plate, orbital roof, and planum sphenoidale were included in the study. The reconstruction technique involved placement of titanium mesh between two layers of continuous vascularized pericranium. Surgical glue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 7 publications
0
31
0
2
Order By: Relevance
“…However, the best method of achieving this is still debated. [5][6][7][8][9][10] Helms and Geyer 11 emphasized the importance of the bony defect closure in addition to the dural repair to prevent CSFLs. They suggested using allografts that strongly hold to the surrounding bone, so that a watertight closure of the skull base bone defect may be achieved.…”
mentioning
confidence: 99%
“…However, the best method of achieving this is still debated. [5][6][7][8][9][10] Helms and Geyer 11 emphasized the importance of the bony defect closure in addition to the dural repair to prevent CSFLs. They suggested using allografts that strongly hold to the surrounding bone, so that a watertight closure of the skull base bone defect may be achieved.…”
mentioning
confidence: 99%
“…Importantly, in neither study had the patients undergone previous surgery or radiation. Interestingly, Badie et al [11] also studied the use of titanium mesh and a pericranial flap alone without fibrin glue to repair large anterior floor defects. Using this strategy, the authors reported a cerebrospinal fluid leak rate of 15%.…”
Section: Anterior Skull Base Reconstructionmentioning
confidence: 98%
“…Whereas nonvascularized bone grafts, alloplastic implants, and HAC successfully reconstruct small bony defects, titanium mesh is well suited for reconstructing large areas requiring structural support to prevent meningoencephalocele [13,23]. Desirable properties include lack of donor site morbidity, malleability, biologic inertness, and MRI compatibility [23,24].…”
Section: Nonvascularized Tissuementioning
confidence: 98%